TOPIC: SOCIAL AND TERRITORIAL DIFFERENTIATION OF VOCABULARY - Istamova Shahnoza; Iskanova Nasiba (TADQIQOTLAR.UZ, 2024)
The study of language and its usage has long captivated researchers, revealing insights into human communication and societal dynamics. A significant area of focus within this field is the social and territorial differentiation of vocabulary. This phenomenon explores how language usage varies among diverse social groups and geographical regions, illuminating the complex relationship between language, identity, and social structures. The social and territorial differentiation of vocabulary encompasses the distinct linguistic patterns and word choices observed within specific social communities and geographic areas. Language is not a fixed entity; it evolves and adapts to the needs and experiences of its speakers. Consequently, individuals belonging to different social groups, such as various age groups, ethnicities, socioeconomic backgrounds, or professions, develop unique sets of vocabulary that reflect their shared experiences, values, and cultural practices.